PEERS, PERSPECTIVES, AND FINANCIAL CHOICES: A STUDY ON FINANCIAL BEHAVIOR AMONG ECONOMICS STUDENTS - Nikmatul, Rowiya; Makhdalena, Makhdalena; Indrawati, Henny (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
Financial behavior is an action that aids individuals in managing their finances effectively. This study aims to analyze the impact of financial attitudes and peer influence on financial behavior, with financial literacy as a mediating factor among students. Conducted from February to June 2023 in the Economics Education Study Program at Universitas Riau, this research collected data through questionnaires and documentation. A total of 115 students participated, selected using a saturated sampling technique (census). Participants included undergraduate students in the 2020 class from Accounting, Cooperatives, and SMEs courses. Data analysis utilized Structural Equation Modeling (SEM) based on variance, specifically Partial Least Square (PLS), with SmartPLS 4.0 software, and an independent T-test on SPSS to assess gender differences in peer influence. The results indicated that financial attitudes and peer influence affect financial behavior through financial literacy. Furthermore, gender differences were observed in financial behavior, influencing decision-making. Therefore, students are encouraged to develop positive financial attitudes and surround themselves with financially knowledgeable peers to enhance their financial decision-making skills.